2015
DOI: 10.1002/sim.6626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two treatments with skewed ordinal responses

Abstract: In clinical studies, the proportional odds model is widely used to compare treatment efficacies when the responses are categorically ordered. However, this model has been shown to be inappropriate when the proportional odds assumption is invalid, mainly because it is unable to control the type I error rate in such circumstances. To remedy this problem, the latent normal model was recently promoted and has been demonstrated to be superior to the proportional odds model. However, the application of the latent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 18 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…A final remark regarding the LNM relates to the estimation of thresholds. As explained by Lu , extensive simulation studies have indicated that the test result is not affected by the choice of treatment for the initial step in estimating the thresholds when the sample is large. For both examples discussed in this paper, we select each of the treatments for use in the initial step to provide estimated thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…A final remark regarding the LNM relates to the estimation of thresholds. As explained by Lu , extensive simulation studies have indicated that the test result is not affected by the choice of treatment for the initial step in estimating the thresholds when the sample is large. For both examples discussed in this paper, we select each of the treatments for use in the initial step to provide estimated thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12 However, a recent study by Lu et al. 13 has reported that although the performance of the latent normal model is satisfactory in most situations, it also suffers from a lack of control of the type I error rate in certain extreme cases when treatment efficacies are compared, specifically, when the degrees of skewness of the treatments differ greatly.…”
Section: Latent Weibull Modelmentioning
confidence: 99%
“…To provide a better model to cope with the problem of the inflated type I error rate for a wider spectrum of data environments, Lu et al. 13,14 suggested the latent Weibull model. The Weibull distribution is a member of the log-location-scale distribution family, and its corresponding distribution in the location-scale family is the extreme value distribution.…”
Section: Latent Weibull Modelmentioning
confidence: 99%
See 2 more Smart Citations